Research on the construction of a natural gas price index in China - Xinlei Yang; Xiucheng Dong; Zhaoyang Kong; Qingzhe Jiang; Tiedong Wang (Energy Strategy Reviews, 2020)
A natural gas price index (NGPI) can be used by stakeholders to comprehensively evaluate the natural gas market. At present, there is no NGPI to measure the volatility of China's entire natural gas market. As a result, when studying the status and trend of natural gas industry, Chinese researchers can reference only the NGPIs compiled by international companies such as Platts and Argus. Therefore, based on the development status of its natural gas industry, this study builds an NGPI for China. The NGPI designed here mainly includes an LNG cost, insurance, and freight (CIF) index, inter-provincial gate station price index, LNG liquefaction plant price index, and unconventional gas price index. The inter-provincial gate station price index consists of residential pipeline gas price index and industrial pipeline gas price index. The unconventional gas price index comprises direct-supply gas price index, shale gas price index, coal gas price index, coalbed methane price index, and tight gas price index. The index design method in this study provides a useful reference for the construction of NGPIs for China in the future.